METHODOLOGIES APPLIED TO INTERNATIONAL MIGRATION AT THE BORDER: REGISTRATIONS AND INVISIBILITIES - Marco Aurélio Machado de Oliveira; Renata Miceno Papa de Almeida; Gilberto Gilberto Xavier Loio; Junior Rodrigues dos Santos Rosales (Revista Tempo do Mundo)
This article aims to demonstrate the potential that the Cadastro Único para Programas Sociais (CadÚnico) records have for reaching international migrants who are invisible due to their documented status, providing rich data on the conditions in which they live, in addition to the uses of other public policies. This is a study developed by the Border Observatory of International Migrations (Migrafron) in the city of Corumbá, MS, Brazil. We used the action research methodology, especially with regard to the application and transfer to the professional environment targeted by the investigations. To this end, employees of the Municipal Department of Social Welfare and Citizenship of that municipality took part in the implementation of this project. We also adopted the procedure of conducting an investigation into the historical contexts of international migration in that city. We started from the observation that the records produced by agencies linked to high politics are limited to international migrants who are regularized in the national territory, and that this constitutes an obstacle to the development of policies that serve them. The methodologies adopted consisted of a literature review on the State’s thinking, especially on invisibility and vulnerability, key categories of analysis in the routine related to CadÚnico, and the application of methods different from those routinely applied in professional environments, especially through the capture of data on the profiles and uses of public systems by international migrants, which allowed for broader views of their presence in the available databases. The results obtained demonstrated that the civil servants, by having differentiated access to CadÚnico data, obtained important aspects that increase the vulnerabilities of international migrants. From this research, it was possible to point out that one of the possibilities for dealing with the issue is to improve the provision of services and the development of care plans aimed at mitigating social risks, through access to documentation, fluency in Portuguese and alternatives for generating stable and secure family income.